Pengembangan Soal Serupa Trends in International and Mathematics and Science Study (TIMSS) untuk Mengukur Kemampuan Berpikir Kritis dan Pemecahan Masalah pada Konten Data dan Peluang - Yulianto, Muhammad Eko; , Prof. Dr. Budi Murtiyasa, M.Kom (2016)
This research aims to develop a similar problem on the TIMSS data content and chance are valid and practical. The method used in this research is research and development. The study consisted of two stages: preliminary and formative evaluation that includes self evaluation, expert review, one-to-one, small group, and a field test. The technique of data collection are walkthrough, document, test, and interview. The subjects in this study is grade 8 students SMP Negeri 1 Surakarta. Results of the research is a similar problem in the TIMSS data content and chance are valid and practical. The test results critical thinking skills and problem-solving at the stage of field test is 4 students (16%) fall into the category of excellent, 8 students (32%) fall into good category, 9 students (36%) fall into the category of fair, 4 students ( 16%) belong to the low category. The test results obtained by the average value of critical thinking skills and problem solving 66.6 included in either category. Based on these results, the test developed declared valid and practical and has a potential effect to measure the ability of critical thinking and problem solving students.